RESEARCH ON APPLICATION- ORIENTED ELECTROMECHANICAL TALENTS’ TRAINING MODE UNDER BACKGROUND OF “INTERNET+ MADE IN CHINA 2025” PROMOTION PLAN - Wang, Fan; Huang, Xiaodong (MATTER: International Journal of Science and Technology, 2018)
China’s economic and social development and the popularization of higher education have led to the development of applied undergraduate education. Innovative and applied undergraduate talents training mode has become an important task to implement quality engineering and improve teaching quality of undergraduate course. Based on the “Internet+ Made in China 2025” Promotion plan sponsored by National Center for Schooling Development Program，this paper explores the Key problem of how to increase the comprehensive application ability and occupational suitability in Application- Oriented Colleges and Universities wherein the education model, college- Enterprise cooperation platform, Platform of practice teaching and curricular system have been further discussed by focusing on the Reformation of theoretical education system, practical teaching system and teaching method. This paper proposed a model of innovative talents training based on college- Enterprise cooperation in electromechanical speciality. Through the construction of modular applied theory teaching system and the practice teaching system based on the cooperation of industry and enterprise to train students’ comprehensive application ability and engineering practice ability, to put forward higher requirements of scientific and technological innovation consciousness, and to cultivate the high skilled talents needed for industrial transformation and upgrading. A sharing mechanism of the Intelligent Manufacturing Internship Factory for the full use of practical teaching environment with the advantages of a cross-regional resource sharing has been also proposed.